2018
DOI: 10.1634/theoncologist.2017-0674
|View full text |Cite
|
Sign up to set email alerts
|

CheckMate 141: 1-Year Update and Subgroup Analysis of Nivolumab as First-Line Therapy in Patients with Recurrent/Metastatic Head and Neck Cancer

Abstract: Nivolumab significantly improved overall survival (OS) vs investigator's choice (IC) of chemotherapy at the primary analysis of randomized, open-label, phase 3 CheckMate 141 in patients with recurrent or metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN). Here, we report that OS benefit with nivolumab was maintained at a minimum follow-up of 11.4 months. Further, OS benefit with nivolumab vs IC was also noted among patients who received first-line treatment for R/M SCCHN after progressing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 9 publications
(13 reference statements)
0
62
0
1
Order By: Relevance
“…Three studies reported on the same population from the CheckMate‐141 clinical trial. The primary CheckMate‐141 study reported outcomes in 2016 and had two subsequent one and two year follow‐ups. These studies were deemed appropriate for inclusion because they collectively presented a complete dataset on one unique cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported on the same population from the CheckMate‐141 clinical trial. The primary CheckMate‐141 study reported outcomes in 2016 and had two subsequent one and two year follow‐ups. These studies were deemed appropriate for inclusion because they collectively presented a complete dataset on one unique cohort.…”
Section: Resultsmentioning
confidence: 99%
“…2 In a landmark analysis, the median OS starting week 6 after RECISTdefined progression was 8.4 months for the TBP group and 3.8 months for the NTBP group. In the context of all patients randomized to receive nivolumab in the trial, this translates to an efficacy benefit of treatment beyond progression in 1.3% (3 of 240).…”
Section: Discussionmentioning
confidence: 98%
“…For 9 of the 15 patients with reductions in the target lesion size (60%), the pharynx was the primary site of disease ( Table 1) Among patients receiving TBP with nivolumab, the median OS was 12.7 months (95% CI, 9.7-14.6 months; Fig. 2 In a landmark analysis, the median OS starting week 6 after RECISTdefined progression was 8.4 months (95% CI, 6.6-10.8 months) in the TBP group and 3.8 months (95% CI, 2.1-5.3 months) in the NTBP group (Fig. In the overall intent-to-treat population (including patients in the TBP and NTBP groups as well as those who did not experience RECIST-defined progression), the median OS for nivolumab-treated patients was 7.7 months (95% CI, 5.7-8.8 months; Fig.…”
Section: Efficacymentioning
confidence: 99%
“…pembrolizumab and nivolumab) have been proved to be safe and effective [27,28,29]. Furthermore, the phase III randomized KEYNOTE-040 trial testing the efficacy of pembrolizumab versus standard treatment (methotrexate, docetaxel or cetuximab) is ongoing (ClinicalTrials.gov Identifier NCT02252042).…”
Section: Discussionmentioning
confidence: 99%
“…Modern agents (i.e. PD-1-receptor antibodies) have been proved to be safe and effective in patients with recurrent or metastatic SCCHN [27,28,29]. …”
Section: Introductionmentioning
confidence: 99%